Widening the spectrum of spinocerebellar ataxia autosomal recessive type 10 (SCAR10). Issue 3 (7th March 2022) - Ásbjörnsdóttir, Birna; Henriksen, Otto Mølby; Lindquist, Suzanne; Møller, Lisbeth Birk; Sidaros, Annette; Nielsen, Jørgen Erik
Abstract : Biallelic pathogenic variants in the ANO10 gene cause spinocerebellar ataxia recessive type 10. We report two patients, both compound heterozygous for ANO10 variants, including two novel variants. Both patients had onset of cerebellar ataxia in adulthood with slow progression and presented corticospinal tract signs, eye movement abnormalities and cognitive executive impairment. One of them had temporal lobe epilepsy and she also carried a heterozygous variant in CACNB4, a potential risk gene for epilepsy. Both patients had pronounced cerebellar atrophy on cerebral magnetic resonance imaging (MRI) and reduced metabolic activity in cerebellum as well as in the frontal lobes on 2-deoxy-2-( 18 F)fluoro-D-glucose positron emission tomography (( 18 F)FDG PET) scans. We provide comprehensive clinical, radiological and genetic data on two patients carrying likely pathogenic ANO10 gene variants. Furthermore, we provide evidence for a cerebellar as well as a frontal involvement on brain ( 18 F)FDG PET scans which has not previously been reported.